Flow-induced vibration handbook for nuclear and process equipment - Pettigrew, M. J.; Taylor, Colette E.; Fisher, N. J. 1959- (Wiley-ASME Press series., 2022)
"Flow-induced vibration is the term for the phenomena of vibration and noise that is caused by fluid flow. Excessive flow-induced vibrations can cause fatigue or failure in process and plant equipment, which can in turn lead to operational disruptions, lost production, and costly repairs. Mechanical engineers can help avoid these issues by performing a flow-induced vibration analysis during the design phase of a project. Industries that employ plants with high capital costs, such as the nuclear, power, petrochemical, and aerospace industries, have a particular interest in understanding and mitigating flow-induced vibrations"--